Long-term Results of the Treatment of Scapholunate Instability with Dynamic Extensor Carpi Radialis Brevis Tenodesis - Frank Nienstedt, MD; Stefan Huber, MD; Markus Mariacher, MD; Erika Vorhauser, OT; Wilhelm Berger, MD (Plastic and Reconstructive Surgery, Global Open, 2023)
Background:. Scapholunate dissociation is the most common form of carpal instability. This retrospective case series aimed to assess long-term results obtained by treating scapholunate instability with dynamic tenodesis using the entire extensor carpi radialis brevis tendon, which is detached from the base of the third metacarpal, rerouted in the third extensor compartment, and fixed at the distal portion of the scaphoid to maintain reduced rotatory subluxation. Methods:. Nine patients with scapholunate instability were treated. We reviewed eight patients with a mean follow-up of 12 years. One subgroup of four patients was affected by static scapholunate instability, and the other by dynamic scapholunate instability. Disability of the Arm, Shoulder, and Hand score, Patient Rated Wrist Evaluation score, modified Mayo score, and radiographs were used to determine functional and anatomical outcomes. Results:. Excellent functional results did not correlate with radiological outcome in patients with static scapholunate instability. In this subgroup, scapholunate angle and gap and radiolunate angle improved in average but remained in the pathologic range. In only one of these patients, osteoarthritis was observed. In the subgroup of patients affected by dynamic instability, very good functional outcomes correlate with radiological results, except in one patient who developed arthritic changes. Conclusions:. Dynamic tethering of the scaphoid with the extensor carpi radialis brevis tendon might be indicated in the treatment not only in patients affected by dynamic scapholunate instability but also in patients with static instability. Prospective studies with a larger number of patients are required to evaluate this method.